Literasi Visual Sebagai Dasar Pemaknaan Karya Audio Visual - Pratiwi, Sri; Balya, Tonna; Prabudi, Reza (Universitas Medan Area, 2019)
The general goal to be achieved in this research is to understand the ability of creators to decipher meanings (interpret) and encode (make) visuals from audio-visual works in the form of a film titled